Determination of radionuclide concentrations in cigarette tobacco by using Thallium-doped NaI (TI) scintillate technique - Dalia Khawwam Kamil; Asma Ahmad Aziz (Tikrit Journal of Pure Science)
This study includes the determination of natural and industrial radionuclides concentrations in different samples of cigarette tobacco. The radionuclides are U238, Th332 series and K40, as well as industrial radionuclides of Cs137.Radiation risk coefficients were calculated. The results showed that the specific activity rates of Ra226, Bi207, Ac228, K40, and Cs137 were within the global limit. The radiological hazard radium equivalent Raeq , intake dose (Dɣ), annual effective dose for external and internal exposure (AEDEout and AEDEin), health risk external and internal hazard indices data (Hex and Hin) and gamma risk radiation were all lower than the allowable global limits.